An asymmetrical whole‐body birdcage RF coil without RF shield for hyperpolarized 129Xe lung MR imaging at 1.5 T. Issue 6 (15th July 2021) - Puddu, Claudio; Rao, Madhwesha; Xu, Xiaojun; Deppe, Martin H.; Collier, Guilhem; Maunder, Adam; Chan, Ho‐Fung; De Zanche, Nicola; Robb, Fraser; Wild, Jim M.
Abstract : Purpose: This study describes the development and testing of an asymmetrical xenon‐129 ( 129 Xe) birdcage radiofrequency (RF) coil for 129 Xe lung ventilation imaging at 1.5 Tesla, which allows proton ( 1 H) system body coil transmit–receive functionality. Methods: The 129 Xe RF coil is a whole‐body asymmetrical elliptical birdcage constructed without an outer RF shield to enable 1 H imaging. B 1 + field homogeneity and flip angle mapping of the 129 Xe birdcage RF coil and 1 H system body RF coil with the 129 Xe RF coil in situ were evaluated in the MR scanner. The functionality of the 129 Xe birdcage RF coil was demonstrated through hyperpolarized 129 Xe lung ventilation imaging with the birdcage in both transceiver configuration and transmit‐only configuration when combined with an 8‐channel 129 Xe receive‐only RF coil array. The functionality of 1 H system body coil with the 129 Xe RF coil in situ was demonstrated by acquiring coregistered 1 H lung anatomical MR images. Results: The asymmetrical birdcage produced a homogeneous B 1 + field (±10%) in agreement with electromagnetic simulations. Simulations indicated an optimal detuning configuration with 4 diodes. The obtained g‐factor of 1.4 for acceleration factor of R = 2 indicates optimal array configuration. Coregistered 1 H anatomical images from the system body coil along with 129 Xe lung images demonstrated concurrent and compatible arrangement of the RF coils. Conclusion: A large asymmetrical birdcage for homogenous B 1 + transmission with high sensitivity reception for 129 Xe lung MRI at 1.5 Tesla has been demonstrated. The unshielded asymmetrical birdcage design enables 1 H structural lung MR imaging in the same exam.